KEPEMIMPINAN PEMERINTAHAN DAERAH DALAM MENDUKUNG IMPLEMENTASI RPJMN 2025–2029 MENUJU INDONESIA EMAS 2045 - Repaldi Ganesa; Bayu Alifta Parhendi; Rendi Revaldo; Akbar Barokah; Okky Danu Wijaya; Eva Susanti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Regional government leadership plays a strategic role in supporting the implementation of the National Medium-Term Development Plan (RPJMN) 2025–2029 as a foundation for achieving Indonesia Emas 2045. This study aims to analyze the role of regional government leadership in supporting the implementation of the RPJMN 2025–2029, identify the synergy between national and regional development, and examine the challenges and leadership strategies required to achieve the vision of Indonesia Emas 2045. This research employs a qualitative method with a library research approach, utilizing data from laws and regulations, books, scientific journals, and official development planning documents. Data were analyzed using a descriptive qualitative approach through data reduction, data presentation, and conclusion drawing. The findings indicate that regional government leadership plays a crucial role in aligning regional development plans with the RPJMN, improving governance quality, developing human resources, strengthening regional economies, and promoting digital transformation and public service innovation. However, the implementation of the RPJMN still faces several challenges, including limited bureaucratic capacity, regional development disparities, fiscal constraints, and intergovernmental coordination issues. Therefore, visionary, adaptive, innovative, and collaborative leadership is essential to support the success of national development. Strong synergy between the central and regional governments is expected to ensure that the implementation of the RPJMN 2025–2029 serves as a solid foundation for realizing Indonesia Emas 2045.